Case Report: Congenital gingival angiomatosis in a newborn lamb - Zapico, D.; Pérez, V.; Criado, M.; Mendívil, P.; Silva, M.; Benavides, J.; Ferreras, M. C.; Espinosa, J. (Frontiers in Veterinary Science, 2025)
Proliferative vascular disorders are rare congenital tumor-like lesions that arise from anomalies in blood vessel development. A newborn Assaf lamb presented with a diffuse, multinodular, dark-red overgrowth of the periodontal gingiva, accompanied by refusal to suckle. The animal developed diarrhea and died 2 days after birth. Necropsy was performed, and histopathological examination of the oral lesions revealed a marked expansion of the gingival stroma by multiple, closely packed, small- to medium-sized vascular channels. These were lined by a single layer of von Willebrand factor- and vimentin-positive endothelial cells and were partially surrounded by alpha smooth muscle actin (α-SMA) - and vimentin-positive spindle cells, consistent with well-differentiated capillaries and post-capillary venules. Taken together, these findings were consistent with diffuse vascular gingival hamartomatosis/angiomatosis. The congenital nature and distribution of the lesions are supportive of a malformation of the periodontal vasculature.